2020
DOI: 10.11648/j.ijhtm.20200402.11
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Marketing for Sustainable Development in Phayao Province, Thailand

Abstract: Phayao is one of the northern provinces in Thailand. It has variety and unique geographical and cultural tourist attractions with few travellers' knowledge of this fact. In 2011, the province came up with such vision intended to develop tourism under the programme "Safety Agriculture and Sustainable Tourism". The local government created a great deal of tourism plans in order to support tourism activities. However, the results were not successful because those tourism plans lacked tourism marketing understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…HenceKye et al (2014) confirmed accordingly that demographic characteristics were personal information influencing the demand and purchasing of tourism products and services. In addition,Madhyamapurush (2022) studied the factors related to changing behavior of Bangkok residents in the Covid-19 endemic and empirically confirmed the same finding as statistically investigated in this research. Finally, Madhyamapurush (2022) reported that varying demographic characteristics of Bangkok residents in terms of gender, marital status and education significantly revealed changing behavior of NNT in the Covid-19 endemic.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…HenceKye et al (2014) confirmed accordingly that demographic characteristics were personal information influencing the demand and purchasing of tourism products and services. In addition,Madhyamapurush (2022) studied the factors related to changing behavior of Bangkok residents in the Covid-19 endemic and empirically confirmed the same finding as statistically investigated in this research. Finally, Madhyamapurush (2022) reported that varying demographic characteristics of Bangkok residents in terms of gender, marital status and education significantly revealed changing behavior of NNT in the Covid-19 endemic.…”
supporting
confidence: 79%
“…Indeed, this statistical and measurable tool had been used to identify target markets with influential consequence on specific demand and purchasing power. Accordingly, Madhyamapurush (2022)…”
Section: Tourism Motivation Of Fits During the Covid-19 Pandemic In S...mentioning
confidence: 99%